COMPARATIVE ANALYSIS OF WORK PRODUCTIVITY THROUGH THE OVERALL EQUIPMENT EFFECTIVENESS (OEE) METHOD - Chaerudin, Abdul Rauf; Abdurrasyad, Rayhan (Bina Bangsa International Journal of Business and Management, 2024)
In an effort to increase employee work productivity, not only rely on the quality of the products produced, but companies or institutions also need to pay attention to factors that influence employee work productivity at PT. XYZ Serang Banten, such as labor and the work environment. Labor is one of the factors that contributes to increasing productivity, with quality labor the production process activities will run as expected by the company, if the labor does not work well then the production process will be disrupted and the results achieved by the company will not be optimal or less productive. By paying attention to factors that can influence the level of employee work productivity, companies can better know and understand the needs and desires of their employees so that employees can feel more satisfied or more cared for and can carry out their work activities optimally.   The aim of the research is to compare productivity between work teams in the assembling division PT. XYZ Serang Banten using the OEE (Overall Equipment Effectiveness) method. Where the results per lot that have been worked on are recorded and entered into the OEE data table.   The method used in collecting this data is a descriptive method, where the problem solving procedure that is investigated is by describing the condition of the subject or object in the research, which can be people, institutions, society and others which are currently based on visible facts or what they are. This method carried out through surveys, where investigations are carried out to obtain facts from existing phenomena and seek factual information, whether about the social, economic or political institutions of a group or region. And the type of data is qualitative because this data can use words to describe facts and phenomena observed from primary data obtained through interviews and observations.             The research results of each team of the 3rd shift assembling division PT. XYZ Serang Banten on the preparation of kraft and decor paper which the operators arranged for one month using the OEE method calculation results were an average productivity of 70%. The highest average productivity was obtained by team C with a total average productivity of 74% , and 73% was obtained by teams B and D. Meanwhile, the lowest average productivity was obtained by team A